2019
DOI: 10.4274/tnd.galenos.2018.81904
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Endothelial Dysfunction and Cerebral Imaging in Migraine

Abstract: Objective: Despite its high prevalence, the basic pathophysiologic mechanism of migraine is still poorly understood. Our aim was to research endothelial dysfunction in patients with recently diagnosed episodic migraine, and to determine whether there was a correlation between endothelial dysfunction and white matter lesions (WMLs) on magnetic resonance imaging (MRI). Materials and Methods: This study was conducted between 2013 and 2014. A total of 51 patients and 27 healthy controls were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In Han et al 36 and Tvedskov et al, 21 8.3% and 33.3% of the patients had menstrual migraine, respectively, with no association detected between menstrual migraine and the neuropeptide plasma level. D'Andrea et al 37 considered different phases of the menstrual cycle in non‐menstrual migraine patients, Caproni et al 38 and Juhasz et al 39 only assessed women in the follicular phase, and Fekrazad et al 40 and Sacmaci et al 41 only included women outside the menstruation period.…”
Section: Resultsmentioning
confidence: 99%
“…In Han et al 36 and Tvedskov et al, 21 8.3% and 33.3% of the patients had menstrual migraine, respectively, with no association detected between menstrual migraine and the neuropeptide plasma level. D'Andrea et al 37 considered different phases of the menstrual cycle in non‐menstrual migraine patients, Caproni et al 38 and Juhasz et al 39 only assessed women in the follicular phase, and Fekrazad et al 40 and Sacmaci et al 41 only included women outside the menstruation period.…”
Section: Resultsmentioning
confidence: 99%
“…The reported prevalence of WMHs in migraine varies widely across studies, ranging from 9.9 % to 78.4 % ( Honningsvåg et al, 2016 , Sacmaci et al, 2019 ). The correlations between WMHs and demographics or migraine characteristics (e.g., migraine subtypes and attack frequency) are also inconsistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have reported increased cerebral blood flow (CBF) in migraine patients 30 . Following elevated CBF, NO production in endothelial cells increases as a response to shear forces and leads to flow-mediated dilation (FMD); thus, it can increase inflammatory responses 28 , 31 , 32 . Increased NO levels have been demonstrated in both migraines with and without aura 33 .…”
Section: Introductionmentioning
confidence: 99%